Nilai-Nilai Pendidikan Islam dalam Hadis tentang Menuntut Ilmu: Kajian Tafsir Hadis Perspektif Tarbawi - Sahrinal Adiansa Hasibuan (LPPI Yayasan Almahmudi bin Dahlan, 2026)
This research aims to comprehensively examine the Islamic educational values embedded within hadiths concerning the pursuit of knowledge, employing a hadith interpretation approach from a tarbawi (educational) perspective. The prevalent phenomenon of limited public understanding regarding the urgency and ethics of seeking knowledge motivates this study to delve into the primary sources of Islamic teachings. The methodology employed is qualitative descriptive, utilizing a literature review approach, which involves the selection, collection, analysis, and interpretation of relevant hadith texts along with their exegesis works. The key findings of this study reveal that hadiths on the pursuit of knowledge are rich in fundamental tarbawi values, encompassing the obligation of seeking knowledge for every Muslim, the importance of sincere intention, the virtues of patience and humility in the learning process, and the encouragement to act upon acquired knowledge. This study concludes that a comprehensive understanding of these hadiths through tarbawi exegesis can serve as a robust foundation for building an effective and character-driven Islamic educational system, thereby shaping individuals who are knowledgeable and faithful.